Kinetic model of the COMPASS tokamak SOL. (March 2021) - Tskhakaya, D.; Adamek, J.; Dimitrova, M.; Hromasova, K.; Seidl, J.; Sos, M.; Vondracek, P.
Highlights: Kinetic effects are significant in the inner divertor plasma. Parallel heat flux in the entire SOL is strongly non-local. Normalized power loads to the ID are above the classical values and are caused by non-Maxwellian super-thermal electrons. Different divertor current regimes do not influence overall SOL parameters, except those of the divertor sheath. Ions in the divertors plasma are colder than the electrons. Modelling results are in a reasonable agreement with the experimental measurements. Abstract: In this work we report on results of full size kinetic modelling of the COMPASS tokamak SOL. Presented simulations indicate, that i. kinetic effects are significant in the inner divertor (ID) plasma; ii. normalized power loads to the ID are above the classical values and are caused by non-Maxwellian super-thermal electrons; iii. different divertor current regimes do not influence overall SOL parameters, except those of the divertor sheath; iv. ions at the divertors plasma are colder than the electrons; v. parallel heat transport is strongly non-local. Modelling results are in a reasonable agreement with the experimental measurements.